Zakat sebagai Sumber Investasi - Djawahir Hejazziey (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2011)
Beside as a tool of worship, zakah can be a source of productive economic development tools for the poor. Zakah is expected to improve the economy of the poor. So, there is a norm that states, zakah aimed at not only circulate wealth among the wealthy. If the property is still managed for consumptive purposes, of course they will spend it just to the rich. Therefore, zakah should be developed in the form of investment so that the profits of fixed assets flow to mustahiq zakah.DOI: